Czech Republic : Financial System Stability Assessment Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper presents a financial system stability assessment update for the Czech Republic. The financial system is confronted with a number of growing risks. Owing to a high reliance of the Czech economy on exports to European Union (EU) countries, the main risk stems from negative developments in EU countries. The results of stress tests show that Czech banks can withstand substantial shocks. The paper reports that the regulatory and supervisory framework for financial institutions is generally sound, although inadequate resources are a major weakness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Czech Republic